Pengembangan Media Monopoli Bahasa Berbantuan Flash Card Digital - Revana Azizah; Satriyani, Febrianti Yuli (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This study aims to develop, assess the feasibility, and test the effectiveness of the Monosa (Language Monopoly) learning media supported by Digital Flash Cards to improve emergent reading skills of first-grade students at SDN Kayu Putih 03. The research employed a Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Validation results indicate that the Monosa media was rated